Serotype-specific host proteome remodeling in human foreskin fibroblasts during lytic HSV-1 and HSV-2 infection - Xiaohong Pan; Jiaxin Xie; Zhidan Zhang; Xiaomei Guo; Jixiong Li; Di Lin; Ying Qian; Jingwen Xu; Yunzhang Hu; Jiandong Shi (Virology Journal)
Abstract Herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2) exhibit distinct clinical manifestations, yet the molecular basis of their serotype-specific pathogenicity remains unclear. This study presents a comparative proteomic analysis of human foreskin fibroblast (HFF-1) cells during lytic HSV-1 and HSV-2 infections to elucidate host–pathogen interactions driving differential virulence. Using data-independent acquisition mass spectrometry (DIA-MS), we identified 280 and 219 differentially expressed proteins (DEPs) in HSV-1- and HSV-2-infected cells, respectively. Key DEPs revealed serotype-specific modulation: HSV-1 upregulated antiviral effectors (ISG20, IRF7) while downregulating chemokine signaling (CXCL12, DEF8) and promoting lipid metabolism (PTDSS1). In contrast, HSV-2 upregulated inflammatory effectors (IGHV3-9, SERPINA1), enhanced NF-κB signaling (BCL3), and altered glycometabolism (GYS1, FBN1). Pathway enrichment analysis showed that HSV-1 suppressed inflammatory and antigen presentation pathways to evade immune responses, whereas HSV-2 induced stronger pro-inflammatory responses and metabolic reprogramming related to lipid and glycometabolism. Overall, these findings provide a proteomic roadmap for understanding serotype-specific pathogenesis.